2012
DOI: 10.1371/journal.pgen.1003055
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation and Its Impact on Gene Expression in Drosophila melanogaster

Abstract: Understanding the relationship between genetic and phenotypic variation is one of the great outstanding challenges in biology. To meet this challenge, comprehensive genomic variation maps of human as well as of model organism populations are required. Here, we present a nucleotide resolution catalog of single-nucleotide, multi-nucleotide, and structural variants in 39 Drosophila melanogaster Genetic Reference Panel inbred lines. Using an integrative, local assembly-based approach for variant discovery, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
135
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(165 citation statements)
references
References 61 publications
30
135
0
Order By: Relevance
“…Interactions between sexually dimorphic trans-regulatory environments and species-specific cis-regulatory alleles also were recently observed between D. simulans and D. mauritiana using a different experimental design (Meiklejohn et al 2013), indicating that these effects are not limited to cis-regulatory variants segregating within a species. Furthermore, while our observations are based on a small subset of the genome, the genes used are not enriched for particular functional groups, chromosomal location, or magnitude of cis-regulatory differences (data not shown), suggesting that the set is unbiased and that sex3cis-regulatory variant interactions are common, consistent with Massouras et al (2012). These types of interactions can result, for example, from cis-regulatory variants that affect binding sites for trans-regulatory factors that differ between the two sexes Cooley et al 2012), as was reported for the Drosophila desatF gene (Shirangi et al 2009).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Interactions between sexually dimorphic trans-regulatory environments and species-specific cis-regulatory alleles also were recently observed between D. simulans and D. mauritiana using a different experimental design (Meiklejohn et al 2013), indicating that these effects are not limited to cis-regulatory variants segregating within a species. Furthermore, while our observations are based on a small subset of the genome, the genes used are not enriched for particular functional groups, chromosomal location, or magnitude of cis-regulatory differences (data not shown), suggesting that the set is unbiased and that sex3cis-regulatory variant interactions are common, consistent with Massouras et al (2012). These types of interactions can result, for example, from cis-regulatory variants that affect binding sites for trans-regulatory factors that differ between the two sexes Cooley et al 2012), as was reported for the Drosophila desatF gene (Shirangi et al 2009).…”
mentioning
confidence: 67%
“…Or, put another way, how often do cis-regulatory variants have sex-specific effects? A recent QTL study of expression variation in D. melanogaster found that sex-specific trans-regulatory factors appear to often have different effects on alternative cis-regulatory alleles (Massouras et al 2012).Here, we investigate the magnitude of such cis-by-sex effects and compare them to the frequency and magnitude of cis-by-trans effects from other sources. To do this, we used pyrosequencing (Ahmadian et al 2000) to measure relative allele-specific expression for 11 randomly selected autosomal genes in male and female F 1 progeny from reciprocal crosses between the highly inbred Drosophila melanogaster lines zhr and z30 (Begun and Aquadro 1993;Sawamura et al 1993;Wu et al 1995;Ferree and Barbash 2009;Coolon et al 2012).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, these activity differences are representative of the range of much of the cis-associated SNP expression variation seen in natural populations [34,38]. The observation that metabolic genes, when perturbed modestly in activity, have an effect on lifespan is certainly relevant to discussions of the maintenance of genetic variation in these genes in natural populations, especially as nutrient levels vary geographically and seasonally [38,39].…”
Section: Discussionmentioning
confidence: 97%
“…The DGRP strains are characterized by high genetic (Mackay et al., 2012; Massouras et al., 2012) and phenotypic variation (Ayroles et al., 2009; Durham, Magwire, Stone, & Leips, 2014; Ellis et al., 2014; Harbison, McCoy, & Mackay, 2013; Mackay et al., 2012; Unckless, Rottschaefer, & Lazzaro, 2015). Fly stocks were ordered from the Bloomington Stock Center and are kept in standard molasses/soy‐corn flour/agar media‐containing vials.…”
Section: Methodsmentioning
confidence: 99%